EKSPERIMENTASI MODEL PEMBELAJARAN LC 5E DISERTAI AFL PADA MATERI PRISMA DAN LIMAS DITINJAU DARI ADVERSITY QUOTIENT - Wibowo, Guritno Ari; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research investigated the effect of using Learning Cycle 5E model using AfL in Mathematics course achievement viewed from Adversity Quotient. TheÂ quasi experimentalÂ research design was employed on this research. The technique analysis data used two-way analysis of variance with unbalanced cell frequencies at 0,05 level of significance. The results show as follows 1) LC 5E with AfL model gave better Mathematics course achievement than the one without AfL and conventional model, and LC 5E without AfL gave better Mathematics course achievement than conventional model. 2) The students who are climber have better Mathematics course achievement than camper and quitter, andÂ the students who are camper have similar Mathematics achievement compared to quitter. 3) In LC 5E with AfL model, the climber category students Mathematics achievements are better than the ones who are camper and quitter, and the camper category students Mathematics achievements were better than the ones who are quitter. In LC 5E model, the climber category students Mathematics achievements are better than the ones who are camper and quitter, and the Mathematics achievements of camper category students were similar with the ones who are quitter. In the conventional model, whether climber, camper, or quitter have the same Mathematics course achievement. 4) Mathematics course achievement of climber category students was the same whether when they were given LC 5E with AfL or LC 5E, on the other hand those are better than the conventional model. The students who are camper category had better Mathematics achievement when they were given LC 5E include AfL and LC 5E than when were given conventional model, however those students had the same Mathematics achievement whether when they were given LC 5E or conventional model. The quitter category students had the same Mathematics achievement when they were given LC 5E with AfL, LC 5E, or conventional model.Keywords: Learning model, LC 5E, Assessment for Learning, Adversity Quotient.